2012
DOI: 10.1002/etc.1847
|View full text |Cite
|
Sign up to set email alerts
|

Stormwater input of pyrethroid insecticides to an urban river

Abstract: The American River flows for nearly 50 km through highly urbanized lands surrounding Sacramento, California, USA. Twenty-three streams, drainage canals, or pumping stations discharge urban runoff to the river, with the cumulative effect of nearly doubling the river's flow during rain events. During winter storms, the water column in the most downstream 13-km reach of the river exhibited toxicity to the standard testing species, Hyalella azteca, in 52% of samples, likely because of the pyrethroid insecticide bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
77
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 76 publications
(83 citation statements)
references
References 28 publications
6
77
0
Order By: Relevance
“…Bifenthrin is a pyrethroid pesticide that binds the voltage-gated sodium channels in neurons, and it has been shown to be estrogenic in several species of fish (Brander et al 2012;Wang et al 2007). Recent monitoring studies have identified bifenthrin in concentrations ranging from 1 to 106 ng/L in northern California (Weston and Lydy 2012;Weston et al 2013).…”
Section: Discussionmentioning
confidence: 98%
“…Bifenthrin is a pyrethroid pesticide that binds the voltage-gated sodium channels in neurons, and it has been shown to be estrogenic in several species of fish (Brander et al 2012;Wang et al 2007). Recent monitoring studies have identified bifenthrin in concentrations ranging from 1 to 106 ng/L in northern California (Weston and Lydy 2012;Weston et al 2013).…”
Section: Discussionmentioning
confidence: 98%
“…The concentrations causing significant effects on all three endpoints in both species are within the range of environmentally relevant concentrations as reported in previous monitoring studies in different states of the USA (Anderson et al 2006;Phillips et al 2012;Smith and Lizotte 2007;Werner et al 2010). For example, studies in Californian creeks by Budd et al (2009) and Weston and Lydy (2012) NOEC no observed effective concentration, LC50 lethal concentration resulting in 50 % mortality of the population, EC50 effect concentration resulting in 50 % reduction in growth, SE standard error, C.I.…”
Section: Discussionmentioning
confidence: 71%
“…Model analyses are an important component of risk assessments (e.g., NOAA’s Biological Opinions [17], [18]), providing a transparent framework linking exposure and biological effects. Targeted pesticide monitoring and concurrent toxicity testing are critical for assessing risk of exposure and the toxicity of water and sediments [2], [15], [48], [63], but we also need to better understand how exposures affect prey densities and salmon feeding behavior in the field. By formally including the indirect effects on salmon via their prey and varying the prey community’s resistance and rate of recovery [26], the model helps determine which parameters influence salmon populations most and identifies empirical information needed to expand our understanding of community dynamics acting in these habitats.…”
Section: Discussionmentioning
confidence: 99%